Dynamics of Electroweak Phase Transition in the 3-3-1-1 Model - Dinh Thanh, Binh; Vo Quoc, Phong; Ngoc Long, Hoang (Communications in Physics, 2020)
The bubble nucleation in the framework of 3-3-1-1 model is studied. Previous studies show that first order electroweak phase transition occurs in two periods. In this paper we evaluate the bubble nucleation temperature throughout the parameter space. Using the stringent condition for bubble nucleation formation we find that in the first period, symmetry breaking from \(SU(3)→ SU(2)\), the bubble is formed at the nucleation temperature T=150 GeV and the lower bound of the scalar mass is 600 GeV. In the second period, symmetry breaking from \((SU(2)→ U(1)\), only subcritical bubbles are formed. This constraint eliminates the electroweak baryon genesis in the second period of the model.